Spillovers From Europe Into Morocco and Tunisia - Florea, Daniel (IMF Working Papers; Working Paper ;, 2010)
This paper examines the economic and financial linkages between Morocco and Tunisia and their European partners. Using structural vector autoregressions, we find that growth shocks in European partner countries generate significant responses on growth in Morocco and Tunisia. For Tunisia, exports and, to a much lesser extent, tourism appear to be the major transmission channels. In Morocco, exports, remittances and tourism play relatively equal roles. An analysis with sectoral data supports these results.